A methodological guide to using and reporting on interviews in conservation science research. Issue 1 (11th January 2018) - Young, Juliette C.; Rose, David C.; Mumby, Hannah S.; Benitez‐Capistros, Francisco; Derrick, Christina J.; Finch, Tom; Garcia, Carolina; Home, Chandrima; Marwaha, Esha; Morgans, Courtney; Parkinson, Stephen; Shah, Jay; et al.
Abstract: Interviews are a widely used methodology in conservation research. They are flexible, allowing in‐depth analysis from a relatively small sample size and place the focus of research on the views of participants. While interviews are a popular method, several critiques have been raised in response to their use, including the lack of transparency in sampling strategy, choice of questions and mode of analysis. In this paper, we analyse the use of interviews in research aimed at making decisions for conservation. Through a structured review of 227 papers, we explore where, why and how interviews were used in the context of conservation decision making The review suggests that interviews are a widely used method for a broad range of purposes. These include gaining ecological and/or socio‐economic information on specific conservation issues, understanding knowledge, values, beliefs or decision‐making processes of stakeholders, and strengthening research design and output. The review, however, identifies a number of concerns. Researchers are not reporting fully on their interview methodology. Specifically, results indicate that researchers are: failing to provide a rationale as to why interviews are the most suitable method, not piloting the interviews (thus questions may be poorly designed), not outlining ethical considerations, not providing clear guides to analysis and not critically reviewing their use of interviews. Based on the results of the review, we provide a detailed checklist aimed at conservation researchers who wish to use interviews in their research (whether experienced in using the methodology or not), and journal editors and reviewers to ensure the robustness of interview methodology use.